Microglial activation and progressive brain changes in schizophrenia. (8th January 2016) - Laskaris, L E; Di Biase, M A; Everall, I; Chana, G; Christopoulos, A; Skafidas, E; Cropley, V L; Pantelis, C
Abstract : Schizophrenia is a debilitating disorder that typically begins in adolescence and is characterized by perceptual abnormalities, delusions, cognitive and behavioural disturbances and functional impairments. While current treatments can be effective, they are often insufficient to alleviate the full range of symptoms. Schizophrenia is associated with structural brain abnormalities including grey and white matter volume loss and impaired connectivity. Recent findings suggest these abnormalities follow a neuroprogressive course in the earliest stages of the illness, which may be associated with episodes of acute relapse. Neuroinflammation has been proposed as a potential mechanism underlying these brain changes, with evidence of increased density and activation of microglia, immune cells resident in the brain, at various stages of the illness. We review evidence for microglial dysfunction in schizophrenia from both neuroimaging and neuropathological data, with a specific focus on studies examining microglial activation in relation to the pathology of grey and white matter. The studies available indicate that the link between microglial dysfunction and brain change in schizophrenia remains an intriguing hypothesis worthy of further examination. Future studies in schizophrenia should: (i) use multimodal imaging to clarify this association by mapping brain changes longitudinally across illness stages in relation to microglial activation; (ii) clarify the nature of microglial dysfunction with markers specific to activation states and phenotypes; (iii) examine the role of microglia and neurons with reference to their overlapping roles in neuroinflammatory pathways; and (iv) examine the impact of novel immunomodulatory treatments on brain structure in schizophrenia. Linked Articles: This article is part of a themed section on Inflammation: maladies, models, mechanisms and molecules. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2016.173.issue-4